PLATELET-RICH PLASMA (PRP): USE IN WOMEN WITH IMPAIRED REPRODUCTIVE FUNCTION, AFTER MISSED MISSCARIAGE - Fazilova , Maxshura (Medical science of Uzbekistan, 2024)
In this study, we used a new method of endometrial restoration with platelet-rich plasma and the effect of plasma on the endometrium was proven. The purpose of the study is to evaluate the efficacy of platelet-rich plasma (PRP) on the endometrium. The research methods included clinical-anamnestic, clinical-laboratory, ultrasound with the use of Doppler, enzyme-linked immunosorbent assay and statistical. Results of the study: A total of 80 women with a history of NB were examined and studied prospectively, divided into two subgroups: IA – 40 patients who received complex treatment with plasma therapy as part of preconception preparation, in this group, 33 patients with pregnancy underwent clinical observation up to 22 weeks; Ib – 40 patients who received standard therapy. The control group consisted of 50 healthy pregnant women up to 22 weeks without a burdened obstetric history - no history of miscarriage. Conclusion: Thus, after complex treatment, including sweat therapy, there was a restoration of hemodynamics at all levels of the vascular tree of the uterus. The main advantage was proven by the onset and favorable course of pregnancy in 82.5% of cases.